The System of Determinants of the Process of Moral Culture Formation of the Teenager Personality in the Conditions of an Orphanage - L F Soldatkina (Peoples' Friendship University of Russia (RUDN University), 2008)
The article characterizes natural (biological), social, pedagogical factors influencing moral culture of the personality of a teenager. The connection of natural (biological) factors with the heredity, social factors - with environment components, pedagogical factors - with the organization of educational process and the personality of the teacher is shown. Their specificity with reference to the given category of children in institutions for orphans is proved.